(untitled) (El-Wahat Journal for Research and Studies, 2017)
Elia Abu Madi Is One Of The Most Prominent Arabic Diaspora In America. He Has Partaken In Formation Of The Pen League, A School Is Said To Have Ushered Arabic Literature From Its Age Old Classicism Into The Modern Era. Abu Madi’s Poems Characterized By Focusing On The Nature’s Beauty, Meditative And Spiritual Tendencies, And Affections Toward Homeland, Woman, And Family. In The Light Of Abu Madi’s Rich And Fertile Creative Experience, It Brings Multidimensional Literary Criticism, That’s Why The Stylistic Devices In His Works Called To Be Studied, Stylistics Includes; Motif, Paradox, Dialogue, And Personification. Keywords – Elia Abu Madi , Stylistic , Poetry , Paradox, Dialogue